Stemborer‐induced rice plant volatiles boost direct and indirect resistance in neighboring plants - Chengcheng Yao; Lixiao Du; Qingsong Liu; Xiaoyun Hu; Ye, Wenfeng; Turlings, Ted; Yunhe Li (My University, 2022)
- Herbivore-induced plant volatiles (HIPVs) are known to be perceived by neighboring plants, resulting in induction or priming of chemical defenses. There is little information on the defense responses that are triggered by these plant–plant interactions, and the phenomenon has rarely been studied in rice. - Using chemical and molecular analyses in combination with insect behavioral and perfor- mance experiments, we studied how volatiles emitted by rice plants infested by the striped stemborer (SSB) Chilo suppressalis affect defenses against this pest in conspecific plants. - Compared with rice plants exposed to the volatiles from uninfested plants, plants exposed to SSB-induced volatiles showed enhanced direct and indirect resistance to SSB. When sub- jected to caterpillar damage, the HIPV-exposed plants showed increased expression of jas- monic acid (JA) signaling genes, resulting in JA accumulation and higher levels of defensive proteinase inhibitors. Moreover, plants exposed to SSB-induced volatiles emitted larger amounts of inducible volatiles and were more attractive to the parasitoid Cotesia chilonis. - By unraveling the factors involved in HIPV-mediated defense priming in rice, we reveal a key defensive role for proteinase inhibitors. These findings pave the way for novel rice man- agement strategies to enhance the plant’s resistance to one of its most devastating pests.
Keywords: Chilo suppressalis; Cotesia chilonis; defense priming; herbivore-induced plant volatiles (HIPVs); jasmonate (JA); proteinase inhibitor (PI)